Iras Perunding Consultant Sdn Bhd / Nur Atika Ismail - Ismail, Nur Atika (UiTM Johor Cawangan Kampus Pasir Gudang, 2014)
Malaysia has gone through incredible changes throughout these 58 years of Independence. It has proudly improve itself from various aspects; politically, economically and sociality. Malaysia now has moved forward into development eastern and western countries. With the development of Malaysia, the government nowadays had introduce the new learning syllabus, which is all engineering student must undergo Industrial Training during the semester break in order to achieve the country’s objective.